DOES ORGANIZATIONAL COMMITMENT MATTER? LINKING TRANSFORMATIONAL LEADERSHIP WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Novianti, Khusnul Rofida (Jurnal Aplikasi Manajemen, 2021)
This research was conducted to identify the antecedents dimension of organizational commitment that consist of affective, continuance, and normative commitment to mediate transformational leadership on organizational citizenship behavior (OCB) in the salespeople's banking sector in Malang, East Java. The population of this research was the employees in the banking sector that provides insurance and investment services in Malang city. The sampling technique used was non-probability sampling. A questionnaire was used as a research instrument. 118 responses were analyzed using Smart Partial Least Square software (Smart-PLS). The study result revealed that organizational commitment does not significantly affect OCB. The affective commitment was the best predictor in mediating the effect of transformational leadership on OCB. In contrast, continuance and normative commitment have an insignificant effect both directly and indirectly on OCB. This study was expected to be a reference for further research in the area of organizational outcome focused on organizational commitment and provide more information for decision making about the importance of leadership styles such as transformational leadership and organizational citizenship behavior.